Choosing bachelor degree programmes for Universiti Teknologi MARA diploma students using fuzzy PROMETHEE / Nur Adriana Batrisyia Mohd Subri - Mohd Subri, Nur Adriana Batrisyia (2021)
Diploma students who want to pursue their studies in bachelor’s degree have to make an important decision which is choosing a programme that they want to study in. This is a tough decision because it involves their future. Furthermore, there are many programmes that are available to choose from as well as many criteria that need to be considered which add to the complication of humans’ subjective thinking and uncertain minds. This study aimed to rank a list of selection of bachelor’s degree programmes in Mathematical Sciences and to compare fuzzy decision with the original decision. Five Mathematical Sciences Bachelor’s Degree Programmes had been taken into consideration namely Mathematics, Actuarial Sciences, Statistics, Computational Mathematics and Management Mathematics. These Mathematical Sciences Bachelor’s Degree Programmes were ranked based on four criteria which are interest, ability, parent’s influence and career opportunities. A final semester student of Diploma in Mathematical Sciences at Universiti Teknologi MARA Perlis was selected as the decision maker for this study. The ranking was done using fuzzy PROMETHEE method. It was found that the most preferred programme by the diploma student was Bachelor of Science in Mathematics and the least preferred programme was Bachelor in Actuarial Sciences. The comparison result showed that the student was certain about his first, second and last choice but was confused about his third and fourth option. This study proved that fuzzy PROMETHEE can help overcome the confusion. Diploma students who are in dilemma to choose programmes for their bachelor’s degree study can definitely benefit from this study.